2017
DOI: 10.1287/mnsc.2016.2510
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Managerial Ability in Corporate Tax Avoidance

Abstract: Most prior studies model tax avoidance as a function of firm-level characteristics and do not consider how individual executive characteristics affect tax avoidance. This paper investigates whether executives with superior ability to efficiently manage corporate resources engage in greater tax avoidance. Our results show that moving from the lower to upper quartile of managerial ability is associated with a 3.15% (2.50%) reduction in a firm’s one-year (five-year) cash effective tax rate. We examine how higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
255
5
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(340 citation statements)
references
References 58 publications
26
255
5
12
Order By: Relevance
“…Since then, researchers have focused primarily on observable CEO characteristics including early life experiences, education, military service, personal investment style, and physical traits such as gender and height. 6 Existing literature examining the impact of managers on investment policy (e.g., Bertrand and Schoar 2003;Benmelech and Frydman 2015), financial policy (Pan, Wang, and Weisbach 2014), firm performance (Adams et al 2005;Andreou, Ehrlich, Karasamani, and Louca 2015), initial public offerings (Chemmanur and Paeglis 2005), compensation (Graham, Li, and Qiu 2012;Cust odio and Metzger 2013), accounting choices (Bamber, Jiang, and Wang 2010;Ge, Matsumoto, and Zhang 2011;Demerjian et al 2013;Demerjian, Lewis, and McVay 2016), corporate tax policy (Dyreng, Hanlon, and Maydew 2010;Koester, Shevlin, and Wangerin 2016) and auditor decisions (Krishnan and Wang 2015).…”
Section: Managerial Abilitymentioning
confidence: 99%
“…Since then, researchers have focused primarily on observable CEO characteristics including early life experiences, education, military service, personal investment style, and physical traits such as gender and height. 6 Existing literature examining the impact of managers on investment policy (e.g., Bertrand and Schoar 2003;Benmelech and Frydman 2015), financial policy (Pan, Wang, and Weisbach 2014), firm performance (Adams et al 2005;Andreou, Ehrlich, Karasamani, and Louca 2015), initial public offerings (Chemmanur and Paeglis 2005), compensation (Graham, Li, and Qiu 2012;Cust odio and Metzger 2013), accounting choices (Bamber, Jiang, and Wang 2010;Ge, Matsumoto, and Zhang 2011;Demerjian et al 2013;Demerjian, Lewis, and McVay 2016), corporate tax policy (Dyreng, Hanlon, and Maydew 2010;Koester, Shevlin, and Wangerin 2016) and auditor decisions (Krishnan and Wang 2015).…”
Section: Managerial Abilitymentioning
confidence: 99%
“…Based on the proposition of Robinson and Dechant (1997), it can be concluded that the diversity of the board has better managerial skills in managing the company compared to the characteristics of homogeneous directors. When linked to tax avoidance, Koester's et al, (2016) research has proven that executives who have superior abilities in utilizing company resources efficiently use more tax avoidance measures. This study analyzes how managers who have higher ability reduce tax payments and find they are involved in tax planning activities.…”
Section: Effect Of Gender Diversity Board On the Relationship Betweenmentioning
confidence: 99%
“…Baik, Farber, and Lee () document a positive relation between managerial ability and corporate social responsibility (CSR) performance, suggesting that more‐able managers can also better manage their firms’ CSR performance. Koester, Shevlin, and Wangerin () find that more‐able managers are less likely to engage in corporate tax avoidance activities.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%